Using a NLSI to deliver the Effective Learning Programme: problems and practicalities - Bob Hunter (Information Research: An International Electronic Journal)
In 1996 the University of Lincolnshire and Humberside implemented its Effective Learning programme (ELP). This is delivered by a Networked Learning Support Intranet (NLSI). This paper discusses some of the issues raised in linking NLSI to centralised databases and the changing staff roles within Learning Support required to develop, deliver and support ELP and the NLSI.